Implementasi Manajemen Penyelenggaraan Makanan Berbasis ABCD di Pondok Pesantren Nurul Qur’an Ponorogo Tahun 2025 - Silvi Titasari; Ahmad Kirom (Social Science Academic, 2025)
This article discusses the implementation of food management at the Nurul Qur'an Pakunden Ponorogo Islamic Boarding School. The purpose of this study is to find out the implementation or application of food management which includes a series of activities starting from the planning, organizing, implementation, to supervision stages at the Nurul Qur'an Islamic Boarding School. This research was conducted at the Nurul Qur'an Islamic Boarding School and was conducted from July 16 - August 28, 2025. The research uses the ABCD (Asset Based Community-driven Development) method , which is a method that prioritizes the benefits of assets and potentials that exist and are owned by the Nurul Qur'an Islamic Boarding School. Data collection techniques through observation, interviews, and documentation. The results of the study show that budget planning is still constrained by funds, menus are not based on nutritional standards, the workforce does not have a nutritional background, the implementation does not follow operational standards, and hygiene supervision is still weak.